Anti-inflammatory effects of Viola yedoensis and the application of cell extraction methods for investigating bioactive constituents in macrophages. Issue 1 (December 2016) - Jeong, Yun; Oh, You-Chang; Cho, Won-Kyung; Shin, Hyeji; Lee, Ki; Ma, Jin
Abstract Background Viola yedoensis (VY, Violaceae) is a popular medicinal herb used in traditional eastern medicine for treating lots of diseases, including inflammation and its related symptoms. However, the anti-inflammatory properties of VY have not been demonstrated. In the present study, we investigated the anti-inflammatory effects of VY ethanol extract (VYE) on macrophages and attempted to identify the bioactive components of VYE. Methods We assessed the effects of VYE on secretion of nitric oxide (NO) and inflammatory cytokines such as tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β. In addition, we explored the expression of inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)-2, and changes in heme oxygenase (HO)-1, nuclear factor (NF)-kB, and mitogen-activated protein kinase (MAPK) signaling pathways in RAW 264.7 macrophages stimulated by lipopolysaccharide (LPS). In addition, a rapid and useful approach to identify potential bioactive components in VYE with anti-inflammatory effects was developed using murine macrophage cell extraction coupled with high-performance liquid chromatography tandem mass spectrometry (LC-MS). Results We found that VYE exerted anti-inflammatory activity by inhibiting the production of key inflammation mediators and related products, as well as suppression of HO-1, NF-kB, and MAPK signaling pathway activation in RAW 264.7 cells. In addition, we identified two compounds in VYE via the cell extraction method. Conclusions Our results revealed that VYE exerts anti-inflammatory activities and its detailed inhibitory mechanism in macrophages. Furthermore, we identified bioactive components of VYE.